Analisis Persepsi Mahasiswa terhadap Penggunaan Media Pembelajaran Digital Berbasis Powtoon dan Quizizz dalam Pembelajaran Ekonomi - M. Sahlani Budi; Eriawaty Eriawaty; Sri Rohaetin; Rinto Alexandro (FKIP, Universitas Palangka Raya, 2026)
This study aims to analyze students’ perceptions of the use of digital learning media based on Powtoon and Quizizz in economics learning. The background of this research is the increasing use of digital media in higher education, particularly to support the understanding of abstract concepts and improve student engagement. This research employed a quantitative descriptive approach. The data were collected through a questionnaire distributed to undergraduate students of Economics Education. The instrument consisted of 15 closed-ended statements using a 4-point Likert scale and one open-ended question. The data were analyzed using descriptive statistics by calculating the mean score of each indicator. The results show that students have a positive perception of the use of Powtoon and Quizizz in learning. Powtoon is perceived as helpful in improving understanding and making learning more interesting, while Quizizz enhances motivation, participation, and provides immediate feedback. The combined use of both media creates a more interactive and engaging learning environment. However, several limitations were identified, such as the complexity of animation in Powtoon and time constraints as well as technical issues in Quizizz. In conclusion, the integration of digital learning media such as Powtoon and Quizizz can support more effective and interactive economics learning, although proper design and implementation are still required.